Cyclic allylic carbonates as a renewable platform for protecting chemistry in water. Issue 14 (20th June 2018) - Olsén, Peter; Morvan, Jennifer; Sawadjoon, Supaporn; Shatskiy, Andrey; Johnston, Eric V.; Åkermark, Björn
Abstract : All in water – functional cyclic carbonates as a versatile and renewable protection/deprotection platform. Abstract : The present work explores different cyclic allylic carbonates as a potential class of allylcarbamate precursors. The 5-membered carbonate formed a carbamate with very good thermal and pH stability, which could be cleanly deprotected in aqueous solution, in just 30 min with 2 mol% Pd(OAc)2 as catalyst. The polar nature of the installed motif made it possible to deprotect highly unpolar substrates in water as solvent.